A note on research design - Awang, Yunita; Taib, Azuraidah; Muhammad, Abdul Rahman (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Academicians are important players towards universities' excellence. The tasks of academicians are not confined to teaching alone but also to research. In conducting research, academicians, particularly young or novice researchers, need to understand the research design. The research design is crucial during the academic-research process as it affects the research process itself. It acts as a master plan that describes the plans and procedures for research inclusive of detailed data-collection and analysis methods. The research design "constitutes the blueprint for the collection, measurement, and analysis of data" (Cooper & Schindler, 2011: 139). Thus, the researchers need to be aware of the various research designs and select the most suitable one for any particular research to be undertaken.